INFLUENCE OF SOLVENT EXTRACTION ON TOTAL ANTIOXIDANT CAPACITY OF VERNONIA AMYGDALINA AND LAURUS NOBILIS LEAVES - Igunbor, Christian Okoro; Emeka, Clinton Chidera; Onakurhefe, Patience; Okpoghono, Joel (FUDMA Journal of Sciences, 2026)
Cells in the body are chronically exposed to oxidants from exogenous and endogenous sources. Nevertheless, antioxidants play important roles in neutralising their effects. The present study investigated the total antioxidant capacity (TAC) of aqueous and methanolic leaf extracts of Vernonia amygdalina and Laurus nobilis at concentrations of 100, 200 and 300 µg/mL, under in vitro conditions, using the phosphomolybdenum assay. Data were analysed using a significance level of p < 0.05. Results showed solvent-dependent variations across all tested concentrations. At 100 and 300 µg/mL, V. amygdalina methanol extract showed higher values of 255.70 ± 10.17 mg AAE/g DW and 276.36 ± 17.18 mg AAE/g DW compared to the aqueous extract that exhibited 230.00 ± 13.83 mg AAE/g DW at 100 µg/mL and 246.99 ± 14.94 mg AAE/g DW at 300 µg/mL. Likewise, L. nobilis extracts recorded substantial increases across all tested concentrations (aqueous extracts: 222.16 ± 11.50 to 241.18 ± 10.67 mg AAE/g DW; methanol extract: 224.80 ± 15.37 to 255.15 ± 13.45 mg AAE/g DW). Both extracts displayed notable antioxidant activity, with the methanolic extract exhibiting higher activity than the aqueous extract. This may be attributed to the enhanced solubility and extraction efficiency of phenolic compounds in methanol. The outcome of this study supports the use of both plants in traditional medicine. However, further studies are required to identify the secondary metabolites responsible for the observed antioxidant activity and their potential application in food.